THE DIFFUSIVE TORTUOSITY OF FINE-GRAINED UNLITHIFIED SEDIMENTS - Boudreau B.P. (My University, 1996)
Use of Fick's First Law to estimate solute fluxes is arguably the most common and important calculation related to the geochemistry and environmental chemistry of fine-grained unlithified sediments. In such porous media, the diffusion coefficient in this law must be reduced by the square of the tortuosity to account for the longer diffusive paths. Experimental methods to estimate tortuosity are specialized or time consuming, and not routinely done. An analysis of available data shows that tortuosity, θ, is accurately correlated to readily measured porosity values, φ, through the simple relation: θ2 = 1 ? ln(φ2).